2003
DOI: 10.1016/s0095-0696(03)00022-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of explanations for inconsistencies in responses to second offers in double referenda

Abstract: This paper demonstrates the potential for induced preference experiments to test previously unverified explanations of observed behavior in contingent valuation surveys. The NOAA Panel on Contingent Valuation called for experimental evidence on potential biases in the double referendum format. We test Carson, Groves, and Machina's [6] simple cost uncertainty and weighted averaging explanations of inconsistent responses to follow-up offers in such double referenda against a baseline of certainty and truthful pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…We used the double-bound model rather than an open-ended WTP question format to reduce strategic bias and the elicitation effect (Burton, Carson, Chilton, & Hutchinson, 2003). Several previous studies have also used this method (Zografakis et al, 2010;Lee & Heo, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We used the double-bound model rather than an open-ended WTP question format to reduce strategic bias and the elicitation effect (Burton, Carson, Chilton, & Hutchinson, 2003). Several previous studies have also used this method (Zografakis et al, 2010;Lee & Heo, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Schkade and Payne 1994). Burton et al (2003) who examined the effects of cost uncertainty in a laboratory referendum setting with induced preferences likewise found that cost uncertainty did not affect the choices in expected ways. We are not convinced that our respondents to the majority-rule format fully understood the consequences of this implementation rule for their strategic opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Third, individuals may simply believe that their response is inconsequential. However, based on theoretical grounds, more general claims that the CV referendum protocol is incentive compatible are misleading (Green et al, 1998;Riera, 2003;Burton et al 2003).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations